DETERMINANTS FOR THE ADOPTION OF TECHNOLOGY AND THE CHOICE OF MARKETING CHANNEL FOR RICE SMALLHOLDER FARMERS IN SOUTHEAST NIGERIA - A. B. Ezeibe; Opata; P. Ifeyinwa2and U. O.Chukwuma (Journal of Animal and Plant Sciences, 2020)
This article examines the factors that unravel how the smallholder rice farmers were influenced by contractual engagement and cooperative participation against spot marketing channels for the adoption of technology and market access using a sample of 420 rice farmers in south-east Nigeria. The multinomial logistic regression model was used and the findings of which reveal that age, land size, distance to market, the volume of long grain rice, fertilizer applied, agrochemicals, access to extension agent, distance to the asphalt road and belonging to farmers’ association werefound as significant factors influencing the choice of marketing channels. Spot market predominates as the majority of farm households are still using spot market and there are still high transaction costs and other constraints. Creation of market linkages, technology and access to input and output markets by smallholders was found to be areas of intervention to improve the rice value chain and to mitigate high transaction costs and technology constraints.
Keywords: smallholders; cooperative; rice; market access; contract; technology